The HVAC Project Technologist Competency Profile - Yunus, Faizal Amin Nur; Fauzi,, Muhammad Fawwaz (Online Journal for TVET Practitioners, 2024)
The challenge of Higher Education Institutions (IPT) nowadays is to provide the human capability needed by the industry. There are most local IPT graduates do not have work skills and competencies required in the market and there seems to be a mismatch in the preparation of graduates for the local job. Therefore, the research carried out provides a comprehensive overview of the competency requirements that must be present in the Heat, Ventilation and Air Conditioning (HVAC) Project Technologist. The following may help the graduates of the HVAC Technologist course at University Tun Hussein Onn Malaysia (UTHM) to be more prepared for the working environment. This study uses the Modified Delphi Technique (MDT) approach in order to obtain expert agreement on the construction of the questionnaire instrument. MDT is conducted three rounds. The first round is the process of developing a questionnaire using previous research methods, document analysis and interviews with three experts. Then the second and third round is to distribute the following questionnaire to get approval from seven experts. The data were processed using the Statistical Package for the Social Sciences (SPSS) software to obtain the mean, median and Interquartile Range (IQR) scores for each item. Preliminary research findings in the first round of MDT found 5 domains, 18 elements and 65 items. However, after the second and third round of MDT, it produced a Project Technology competency that has 5 domains, 18 elements and 78 items. The results of this research data are expected to give ideas and insights course content to HVAC Technologist program by looking that matches career competencies according to industry tastes.